Eggshell membrane modulates gut microbiota to prevent murine pre‐cachexia through suppression of T helper cell differentiation. Issue 4 (19th June 2022) - Jia, Huijuan; Lyu, Weida; Hirota, Kazuki; Saito, Eri; Miyoshi, Moe; Hohjoh, Hirohiko; Furukawa, Kyohei; Saito, Kenji; Haritani, Makoto; Taguchi, Akashi; Hasebe, Yukio; Kato, Hisanori
Abstract: Background: Cachexia is a life‐threatening condition observed in several pathologies, such as cancer or chronic diseases. Interleukin 10 ( Il10 ) gene transfer is known to improve cachexia by downregulating Il6 . Here, we used an IL10‐knockout mouse model to simulate cachexia and investigate the effects of eggshell membrane (ESM), a resistant protein, on general pre‐cachexia symptoms, which is particularly important for the development of cachexia therapeutics. Methods: Five‐week‐old male C57BL6/J mice were fed an AIN‐93G powdered diet (WT), and 5‐week‐old male B6.129P2‐Il10 < tm1Cgn>/J (IL10 −/− ) mice were fed either the AIN‐93G diet (KO) or an 8% ESM‐containing diet (KOE) for 28 weeks. The tissue weight and levels of anaemia‐, blood glucose‐, lipid metabolism‐, and muscular and colonic inflammation‐related biochemical markers were measured. Transcriptomic analysis on liver and colon mucus and proteomic analysis on skeletal muscle were performed. Ingenuity Pathway Analysis was used to identify molecular pathways and networks. Caecal short‐chain fatty acids (SCFAs) were identified using HPLC, and caecal bacteria DNA were subjected to metagenomic analysis. Flow cytometry analysis was performed to measure the CD4 + IL17 + T cells in mesenteric lymph nodes. Results: The body weight, weight of gastrocnemius muscle and fat tissues, colon weight/length ratio, plasma HDL and NEFA, muscular PECAM‐1 levels ( P  < 0.01), plasma glucose and colonic mucosal myeloperoxidase activity ( P  < 0.05) and T helper (Th) 17 cell abundance ( P  = 0.071) were improved in KOE mice over KO mice. Proteomic analysis indicated the protective role of ESM in muscle weakness and maintenance of muscle formation (>1.5‐fold). Transcriptomic analysis revealed that ESM supplementation suppressed the LPS/IL1‐mediated inhibition of RXR function pathway in the liver and downregulated the colonic mucosal expression of chemokines and Th cell differentiation‐related markers ( P  < 0.01) by suppressing the upstream BATF pathway. Analysis of the intestinal microenvironment revealed that ESM supplementation ameliorated the microbial alpha diversity and the abundance of microbiota associated with the degree of inflammation ( P  < 0.05) and increased the level of total organic acids, particularly of SCFAs such as butyrate (2.3‐fold), which could inhibit Th1 and Th17 production. Conclusions: ESM supplementation ameliorated the chief symptoms of cachexia, including anorexia, lean fat tissue mass, skeletal muscle wasting and reduced physical function. ESM also improved colon and skeletal muscle inflammation, lipid metabolism and microbial dysbiosis. These results along with the suppressed differentiation of Th cells could be associated with the beneficial intestinal microenvironment and, subsequently, attenuation of pre‐cachexia. Our findings provide insights into the potential of ESM in complementary interventions for pre‐cachexia prevention.